5E learning cycle combined with mind mapping in excretory system: effectiveness on curiosity - Dhani Nugrahaningtyas Utami; Bambang Subali (Biosfer, 2020)
Curiosity is one of the important characters developed in the 21st century. This study aimed to determine the effectiveness of the 5E (engage, explore, explain, elaborate, dan evaluate) learning cycle model combined with mind mapping on the curiosity of XI classes students in the excretion system material. This research was an experimental study with a non-equivalent pretest-posttest control group design. The study population included all students of XI science classes in Yogyakarta, Indonesia that amounted to 96 people. Samples were 32 for experimental as well as control group, with a total of 64 people. The instrument used was a non-test instrument in the form of a questionnaire consisting of 20 items. The validity of the instruments was good, and the reliability was very high, so the instruments were suitable to be used in data collection. Based on the results of data analysis using the Mann Whitney test, it was found that there were significant differences in the use of the 5E learning cycle model combined with effective mind mapping on student curiosity (p: 0.007 <0.05). It is recommended for Biology teachers to use the 5E learning cycle model with mind mapping to improve student curiosity in excretory material.